1983
DOI: 10.1002/art.1780261202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lymphoplasmapheresis on clinical indices and t cell subsets in rheumatoid arthritis a double‐blind controlled study

Abstract: The effects of lymphoplasmapheresis on immunologic indices, including T cell subsets, and on clinical parameters of rheumatoid arthritis were evaluated in a controlled double-blind trial. Twenty patients were randomized to receive either 6 lymphoplasmapheresis sessions or a seemingly identical control procedure over a 3-week period. Lymphoplasmapheresis produced significant reduction in serum levels of total lymphocytes, erythrocyte sedimentation rate, C-reactive protein, and IgG. These serologic measures retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
(7 reference statements)
0
3
1
1
Order By: Relevance
“…The authors speculate that the difference of the recovery time between the Leu3a‐positive cell and the Leu2a‐positive cell brought about a decrease in Leu3a/Leu2a. Although previous studies have showed that the change in Leu3a/Leu2a after LCP was not significant (13,20), these studies were achieved by total removal of only 3–5 × 10 9 lymphocytes, which was much less than the present total removal. The different results between previous studies and the present one seem to be related to differences in the number of removed lymphocytes and the frequency of LCP.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The authors speculate that the difference of the recovery time between the Leu3a‐positive cell and the Leu2a‐positive cell brought about a decrease in Leu3a/Leu2a. Although previous studies have showed that the change in Leu3a/Leu2a after LCP was not significant (13,20), these studies were achieved by total removal of only 3–5 × 10 9 lymphocytes, which was much less than the present total removal. The different results between previous studies and the present one seem to be related to differences in the number of removed lymphocytes and the frequency of LCP.…”
Section: Discussioncontrasting
confidence: 75%
“…It cannot be certain that observed clinical improvement was due to LCP in this uncontrolled study, because placebo effects and spontaneous improvement have not been taken into account. Other studies were underway to determine whether the LCP was effective for RA, but different results were reported (12,20). A properly designed double‐blind controlled study is indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…As for nondrug therapy, leukocytapheresis (LCAP) -a treatment that removes peripheral leukocytes by continuous fl ow cell centrifugation -was found to provide clinical benefi ts in patients with refractory RA. [5][6][7][8][9][10][11] Thereafter, simpler fi ltration LCAP was developed and reported to suppress disease activity in patients with active RA refractory to multiple DMARDs. [12][13][14][15][16] The fi ltration LCAP leads to considerable improvements in joint symptoms and global assessment of disease activity; however, acute-phase indicators such as C-reactive protein (CRP) level and erythrocyte sedimentation rate (ESR) have exhibited limited improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Verdickt et al compared removal of 345 ml plasma per kg together with 5 x 109 lymphocytes six times in three weeks with a sham procedure on a double blind basis. 39 The improvement in laboratory indices was not reflected in clinical benefit. As yet neither lymphocytapheresis nor lymphocytoplasmapheresis has found a place in this or any other immunologically mediated disease.…”
mentioning
confidence: 98%